PENGARUH ONLINE CUSTOMER REVIEW, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN TOKOPEDIA - Faradita, Putri Adriani; Widjajanti, Kesi (Solusi, 2023)
This study aims to determine how much influence online customer reviews, prices, product quality have on purchasing decisions through the Tokopedia marketplace for Tokopedia users in the city of Semarang, there is a problem in making online purchases in the marketplace, including that buyers face various risks when making a purchase decision, where consumers cannot see directly the goods to be purchased, consumers do not know that the goods to be purchased will meet the expected needs or expectations of the product to be purchased. The population in this study were Tokopedia users, with a sample of 96 respondents using purposive sampling and a Likert scale measurement. The analysis in this study was processed using SPSS software. The results in this study show that online customer reviews, prices, and product quality simultaneously influence purchasing decisions on the Tokopedia marketplace. Online customer reviews have a significant effect on purchasing decisions on the Tokopedia marketplace. Prices have a significant effect on purchasing decisions on the Tokopedia Marketplace. Product quality has a significant effect on purchasing decisions on the Tokopedia marketplace. The population defined in this study is Tokopedia users in the city of Semarang. Then through the F test shows that the online customer review variables, price and product quality are appropriate to test the purchasing decision variable. Adjusted R square of 0.719 indicates that 71.9% of the decision to stay variable can be explained through the three independent variables in the regression equation. While the remaining 28.1% is explained by other variables outside the three variables used in this study.